Pengaruh Model Game Based Learning Berbantuan Game Edukasi Scratch dalam Meningkatkan Pemahaman Kosakata Bahasa Inggris - Syavaqilah, Widia; Nurmahanani, Indah; Tiara Antik Sari, Nadia (AS-SABIQUN, 2025)
Vocabulary comprehension is a crucial component in mastering the English language; however, many elementary school students continue to struggle with acquiring basic vocabulary, including topics such as kinds of vehicles. This study aims to determine the effect and improvement of students’ English vocabulary comprehension through the implementation of a Game Based Learning model assisted by the educational game Wheels & Words, developed on the Scratch platform. A pre-experimental method with a one-group pretest-posttest design was used, involving 33 fourth-grade students at SDN 3 Nagrikaler as subjects. Instruments included a pretest, posttest, and observation sheet. The results showed an increase in the average score from 57.81 on the pretest to 79.75 on the posttest. A paired sample t-test indicated a significant difference between pretest and posttest scores, while simple linear regression analysis revealed that 54.4% of the improvement in vocabulary comprehension was influenced by the implementation of the Game Based Learning model assisted by Wheels & Words. The N-Gain analysis showed a gain of 55.56%, categorized as a moderate level of improvement. These findings demonstrate that the use of educational game-based digital media can serve as an effective alternative for enhancing English vocabulary comprehension among elementary students. The study’s implications highlight opportunities for further development of interactive digital media tailored to students’ characteristics and learning needs in foreign language education.